Analisis Maslahah Mursalah Terhadap Dispensasi Nikah Karena Kehamilan di Luar Nikah - A, Abriansyah; A, Ativa; Maloko, M. Thahir (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article analyzes the value of maslahah mursalah in the marriage dispensation for pregnancy out of wedlock. This research study is a type of library research with a normative-empirical legal approach. Meanwhile, the type of data analysis is qualitative-descriptive. This research found that the phenomenon of out-of-wedlock pregnancies for minors is still widespread in social life institutions. One way to get married is to apply for a marriage dispensation. In the marriage dispensation there are maslahah mursalah values, including the community getting legal certainty and justice at the same time as minimizing harm.